ANALYSIS OF ACCOUNTING INFORMATION SYSTEMS IN THE MANAGEMENT OF SCHOOL OPERATIONAL ASSISTANCE (BOS) FUNDS BASED ON THE E-RKAM APPLICATION IN MIS MUHAMMADIYAH 10 CUMPLENG KECAMATAN BRONDONG KABUPATEN LAMONGAN - Putri, Yuli Kartika; Zuraidah, Zuraidah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This research aims to examine the implementation of an accounting information system using the E-RKAM application at the Muhammadiyah Private Madrasah Ibtidaiyah (MIS) 10 Cumpleng, Lamongan Regency. The method used is a descriptive qualitative approach with data collection through observation, interviews and documentation. The research results show that the use of the E-RKAM application has succeeded in increasing effectiveness and efficiency in planning and managing School Operational Assistance (BOS) funds at MIS Muhammadiyah 10 Cumpleng. However, there are challenges in its implementation, such as minimal transaction recording which causes inaccurate financial reports. This evaluation encourages the need for continuous improvements in school financial management, including clearer separation of duties and more detailed transaction recording.